2018
DOI: 10.3390/nu10070801
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Vitamin E Intake and Esophageal Cancer Risk: An Updated Meta-Analysis

Abstract: Epidemiological studies have provided ambiguous evidence on the association between vitamin E and esophageal cancer risk. To resolve this controversy, we performed this meta-analysis. The literature was searched by using Excerpta Medica Database (EMBASE), PubMed, the Web of Science, and the Cochrane Library from the inception to April 2018. A random effect model was utilized to calculate the odds ratio (OR) with the 95% confidence interval (95% CI). Twelve articles reporting 14 studies involving 3013 cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Meta‐analysis by Edefonti et al 77 found an inverse relationship between VE intake and head and neck cancer incidence rates. A meta‐analysis recently completed by Cui et al 78 showed that higher levels of dietary VE were associated with a lowered risk of esophageal cancer .…”
Section: Human Studies On Ve and Cancermentioning
confidence: 99%
“…Meta‐analysis by Edefonti et al 77 found an inverse relationship between VE intake and head and neck cancer incidence rates. A meta‐analysis recently completed by Cui et al 78 showed that higher levels of dietary VE were associated with a lowered risk of esophageal cancer .…”
Section: Human Studies On Ve and Cancermentioning
confidence: 99%
“…Furthermore, dietary factors [7] may affect the risk of esophageal cancer. Previous studies suggested that vitamins intake [8,9], fiber intake [10], folate intake [11,12], could decrease the development of esophageal cancer. Intakes of bioactive compounds from various plant sources also reduced the risk of cancer [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer remained an indispensable cause of cancer-related deaths and had shown a dramatic increase in global morbidity by more than six times [2]. Efforts to identify lifestyle factors [3] that may affect the risk of esophageal cancer had been ongoing, as well as some dietary factors, such as dietary vitamins [4,5], dietary fiber intake [6], dietary folate intake [7,8], total iron and zinc intake [9] and so on, may affect the development of esophageal cancer. Previous studies had been published to assess carbohydrate intake and some cancers risk, such as colorectal cancer [10], breast cancer [11], prostate cancer [12], but no meta-analysis was performed between carbohydrate intake and the risk of esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%